Mechanical behaviour of nano ceramic particles reinforced aluminium matrix composites. (2022) - Surakasi, Raviteja; Rajendra Prasad, A.; Pattnaik, Birajashis; Venkata Rao, M.; Puthilibai, G.; Vibhakar, Chirag; Rajkumar, S.
Abstract: New propulsion materials are becoming increasingly popular as a result of the significant growth in industrial innovation over the last few years. Using nano-sized reinforcement materials in aluminium metal matrix composites, engineers will be able to satisfy new engineering demands. In the automobile and aircraft industries, as well as in general industry, they're widely employed. A base material's mechanical strength, wear resistance, and fracture toughness can all be improved by mixing with hard ceramic nanoparticles. By adopting Ultrasonic-Cavitation assisted casting technique, an Al6061 alloy composite comprising varied weight percentages of B4C nanoparticles (ranging from zero to eight weight percent) was effectively manufactured. Although the hardness, ultimate tensile strength, and yield strength of the material all augmented significantly, the ultimate strength decreased as the concentration of B4C Nanoparticles increased.